Validating Climate Smart Agriculture and One Health Technologies for Improved Climate Resilience and Productivity Throught Piloting - Yeboah, Stephen; Adomako, Joseph; Wadie, Blankson Amoabeng; Frimpong-Annin, Kofi; Amankwaa-Yeboah, Patricia; Martey, Francisca; Clottey, Victor; Damba, Osman Tahidu; Haleegoah, Joyce; Badu-Brempong, Mavis; Dalaa, Mustapha Alasan; Obeng, Faustina; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Building community resilience to climate risk through demonstration plots is a priority in sub-Saharan Africa, where the agricultural system is mainly rainfed and underdeveloped due to multiple underlying causes, such as limited access to information, improved seeds/inputs, modern production practices, and technologies. The use of demonstration plots serve as a platform to promote validated climate-smart and One health technologies.. Under the current project, demonstration plots were used to provide training on good production practices of the various AICCRA-Ghana value chains. Thirty-one (31) demonstration plots were established across eighteen (18) communities in four agroecologies (Coastal savannah, Transition, Guniea savannah, and Sudan savannah) of Ghana. The value chains piloted were maize (13 pilots), yam (6 pilots), cowpea (8 pilots), and sweet potato (4 pilots). These value chains were chosen because of their socio-economic importance in Ghana. Maize and cowpea technologies constituted 42 and 26% of the number of demonstration plots established, respectively. Twenty-one field days were organized to introduce beneficiaries and other stakeholders in the project intervention communities to the various technologies the project demonstrated (i.e climate-smart seeds, One health innovations, and good agronomic practices). A total of One thousand one hundred and thirteen (1113) people were reached out to and directly participated in the field days. Four hundred and fifty-nine of the participants, representing 41% were female. While farmers from intervention communities expressed gratituted to the project, farmers from other communities that participated in the field days have requested for the project to extend such demonstrations to them. Generally, participants expressed their satisfaction and willingness to adopt these new technologies and incorporate them into their farming business next year and beyond.